2016
DOI: 10.1371/journal.pone.0167434
|View full text |Cite
|
Sign up to set email alerts
|

Unique Molecular Patterns Uncovered in Kawasaki Disease Patients with Elevated Serum Gamma Glutamyl Transferase Levels: Implications for Intravenous Immunoglobulin Responsiveness

Abstract: BackgroundResistance to intravenous immunoglobulin (IVIG) occurs in 10–20% of patients with Kawasaki disease (KD). The risk of resistance is about two-fold higher in patients with elevated gamma glutamyl transferase (GGT) levels. We sought to understand the biological mechanisms underlying IVIG resistance in patients with elevated GGT levels.MethodWe explored the association between elevated GGT levels and IVIG-resistance with a cohort of 686 KD patients (Cohort I). Gene expression data from 130 children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Identification of potential non-responders before IVIG treatment using genomic scores (MDTH) in an ethnically diverse population may potentially allow early use of adjunctive therapies in selected patients, which in turn could be associated with improved coronary outcomes [ 6 , 30 ]. Previous studies have utilized whole blood transcriptional patterns to identify specific transcripts that were over-expressed in patients with eventual IVIG resistance [ 36 , 37 ], as well as serum biomarkers and cytokines such as G-CSF and sTNFR1 that were correlated with lack of response to therapy. [ 38 , 39 ][ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of potential non-responders before IVIG treatment using genomic scores (MDTH) in an ethnically diverse population may potentially allow early use of adjunctive therapies in selected patients, which in turn could be associated with improved coronary outcomes [ 6 , 30 ]. Previous studies have utilized whole blood transcriptional patterns to identify specific transcripts that were over-expressed in patients with eventual IVIG resistance [ 36 , 37 ], as well as serum biomarkers and cytokines such as G-CSF and sTNFR1 that were correlated with lack of response to therapy. [ 38 , 39 ][ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finding biomarkers that can predict IVIG resistance is an important area of current KD research. Neutrophils [14,[77][78][79][80][81], B cells [23], CD8+ T cells [82], and Th17 cells [32,33] in KD peripheral blood have all been reported to predict IVIG resistance, but the types of immune cells supported by different studies are not consistent. Our research did not identify immune cells that can accurately predict IVIG response in multiple datasets.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG resistant patients have higher levels of N%, CRP, NT-proBNP, TBIL, ALT, AST and lower levels of L%, PLT. Several previous studies reported that CRP, ESR, ALT, γ-GT and NT-proBNP could be used for predicting resistance to IVIG therapy and patients who are at high risk for CALs [4,[31][32][33][34]. To predict the ability of response to IVIG before initial therapy, would allow clinicians to identify those potential IVIG resistant patients and give them more aggressive treatments [35].…”
Section: Discussionmentioning
confidence: 99%